New Metropolitan Perspectives Knowledge Dynamics, Innovation-driven Policies Towards the Territories' Attractiveness Volume 1 - Bevilacqua, Carmelina; Calabrò, Francesco; Della Spina, Lucia (Smart Innovation, Systems and Technologies, 2020)
​This open access book presents the outcomes of the symposium "NEW METROPOLITAN PERSPECTIVES," held at Mediterranea University, Reggio Calabria, Italy on May 26-28, 2020. Addressing the challenge of Knowledge Dynamics and Innovation-driven Policies Towards Urban and Regional Transition, the book presents a multi-disciplinary debate on the new frontiers of strategic and spatial planning, economic programs and decision support tools in connection with urban-rural area networks and metropolitan centers. The respective papers focus on six major tracks: Innovation dynamics, smart cities and ICT; Urban regeneration, community-led practices and PPP; Local development, inland and urban areas in territorial cohesion strategies; Mobility, accessibility and infrastructures; Heritage, landscape and identity;and Risk management,environment and energy. The book also includes a Special Section on Rhegion United Nations 2020-2030. Given its scope, the book will benefit all researchers, practitioners and policymakers interested in issues concerning metropolitan and marginal areas.